Progression of arterial stiffness and coronary atherosclerosis: longitudinal evaluation by cardiac CT - Oberoi, Shane; Schoepf, U. Joseph; Meyer, Mathias; Henzler, Thomas; Rowe, Garret W.; Costello, Philip; Nance, John W. (American journal of roentgenology, 2013)
OBJECTIVE. We sought to use cardiac CT angiography (CTA) to longitudinally examine the relationship between changes in aortic stiffness and of the atherosclerotic burden over time. - - MATERIALS AND METHODS. One hundred sixty-four patients with suspected coronary artery disease underwent two retrospectively ECG-gated cardiac CTA studies an average of 12 ± 10 months apart. Arterial stiffness was represented by the aortic distensibility index (ADI) and atherosclerosis by segment involvement score (SIS) (defined as the number of coronary artery segments per patient displaying atherosclerotic plaque). Changes in ADI and SIS between the studies were compared using linear and logistic regression accounting for differences in clinical and demographic baseline characteristics. - - RESULTS. Age (p = 0.004), time between studies (p = 0.02), and increase in SIS (p < 0.001) were associated with a decrease in ADI on univariate analysis. Increase in SIS remained a significant independent predictor of decreased ADI on both multivariate logistic regression (with change in ADI represented categorically) and multivariate linear regression (both p < 0.001). - - CONCLUSION. On longitudinal evaluation with cardiac CTA, the progression of aortic stiffness is associated with the progression of coronary atherosclerosis. Although outcome studies are needed, a comprehensive assessment of vascular health with cardiac CTA, including both indexes of arterial stiffness and atherosclerotic burden, may improve risk stratification and therapy monitoring.
Gesehen am 31.03.2022